ANALISIS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) BERBASIS LITERASI KEUANGAN DI SMA NEGERI 1 TOMOHON - Allen Ch. Manongko; Listriyanti Palangda; Mawarta Nania Marisina (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2023)
ABSTRACT This study's goal is to describe in depth the BOS SMA administration at SMA Negeri 1 Tomohon in the coming year of 2022. In this article, we will discuss the following topics in order: (1) planning for SMA BOS finances in SMA Negeri 1 Tomohon; (2) implementation; (3) monitoring and evaluation; and (4) reporting. This research is a qualitative descriptive analysis. Participants in this research comprised school administrators, instructors, and students from SMA Negeri 1 Tomohon. Interviews and careful note-taking are two common data collection methods. The reliability of the data in this study was ensured by the use of triangulation and member checks. Methods for analyzing the data include data reduction, data presentation, and verification of the resulting conclusions. Based on the findings, (1) the SMA Negeri 1 Tomohon school budget team develops the RKAS with input from the School Committee, faculty, and parents of SMA students in order to allocate SMA BOS money for 2022. The RKAS was ready at the same time as the SMA BOS RAB. In 2022, there will be a two-part process for distributing SMA BOS Funds: (2) implementation, and (3) distribution. Collecting funds as the high school's BOS Treasurer. In accordance with the technical specifications laid forth in the SMA BOS 2022, schools may only utilize SMA BOS Funds to cover